Prevalence of Peptic Ulcer Disease in Patients with Chronic Obstructive Pulmonary Disease in a Teaching Hospital (TAJ: Journal of Teachers Association, 2018)
Objective: Chronic obstructive pulmonary disease is major cause of chronic morbidity and mortality throughout the world. Peptic ulcer disease is not uncommon in patients with chronic medical condition like chronic obstructive pulmonary disease. Patients who smoke or have chronic obstructive pulmonary disease carry higher risk of developing peptic ulcer disease. The aim of this study was to saw the prevalence of peptic ulcer disease as well as prevalence variation in relation with severity of chronic obstructive pulmonary disease. Methods: This was cross sectional observational study from January, 2013 to January, 2014 in department of Medicine, Rajshahi Medical College Hospital, Rajshahi who fulfilled the inclusion & exclusion criteria were selected in this study. Data was collected in a prefixed questionnaire form and data collection sheet after taking informed consent of the patient. All the patients were investigated with spirometry, chest X-ray, complete blood count, electrocardiogram, echocardiography and endoscopy upper gastrointestinal tract. Results: Among the study population 100% patient was male. Most of them were 51-60 years (42.4%) with mean aged was 56.48 ± 7.64 years. Endoscopic finding was normal (55, 85.94%), gastritis (02, 3.12%), gastric erosion (03, 4.69%), peptic ulcer (03, 4.69%) and peptic ulcer with active bleeding (01, 1.56%).Prevalence of peptic ulcer disease in this study was 14.06%.Conclusion: Prevalence of peptic ulcer was more in chronic obstructive pulmonary disease patient than normal population. The prevalence of peptic ulcer diseases also increases with the severity of the disease.TAJ 2017; 30(1): 30-35